Development and validation of an implicit test of the HEXACO honesty-humility scale - Van Rensburg, Yolandi-Eloise Jansen (Department of Psychology, 2020)
Honesty-humility, a personality trait in the self-report HEXACO personality inventory outperforms all the traits (also those in the traditional five-factor model) in predicting integrity-related behavior. However, concerns exist that self-report personality measures are vulnerable to socially desirable responding, self-report bias, faking and being prone to testtakers’ lack of introspective accuracy. Therefore, researchers have started using implicit tests to assess personality, as it is more difficult to fake responses. The main goal of this research was to develop and validate an implicit measure for honesty-humility (IAT-HH). Chapter 2 presents the findings of a literature overview, which determined which types of implicit measures can be distinguished, how implicit constructs are operationalized and how implicit tests could be applied in practice. Prior to validating a test, establishing how the construct (predictor) relates to outcomes (criteria) is essential. Therefore, an empirical study was conducted amongst students from a South African university (N = 308). Chapter 3 reports how explicit honesty-humility and the narrow facets it comprises, relate to academic dishonesty criteria (i.e., counter-academic criteria and collegiate cheating). Results found that fairness predicted counter-academic behavior, whilst greed avoidance predicted cheating. Chapter 4 presents the findings of how the IAT-HH was developed, and the results of a second empirical study, which investigated the construct validity of the IAT-HH. In this study, data were collected amongst students from a Flemish university (N = 178) and convergent and discriminant validity were investigated (with explicit honesty-humility, social desirability, ability to identify criteria and cognitive ability). Chapter 5 reports on the criterion-related validity of the IAT-HH. Overall, results showed limited construct validity and negligible criterion-related and incremental validity and, as such, the implicit measurement of honestyhumility remains an elusive goal. Chapter 6 summarizes the key findings and implications of the research. Finally, recommendations for researchers and practitioners, who wish to employ implicit measures of honesty-humility, are outlined.